KAJIAN KOMPUTASI POLA GELOMBANG RESONANSI MAGNET INTI (NMR) DENGAN TRANSFORMASI FOURIER - Faprilia Khusnul; Salomo Salomo; Muhammad Hamdi (Universitas Riau, 2018)
Research on nuclear magnetic resonance (NMR) modeling has been done with computational approach. This study aims to determine the shape of signals and spectra of some of the combined nuclear spins. The physical parameters were determined using Fourier transformation equation modeled with the wolfram mathematical software 9.0. The relaxation time of the 1/2 nuclear spin was varied according to the nuclear state of cancer tissue.This produces a cosine wave pattern for the signal at T2 = 0.11 ms. Variations of this in chemical shift (Δ) and J-coupling (J) for modeling were performed in 9 times. The spectrum of one spin is generated at the value of Δ = 0.001 Hz and J = 0 Hz, the spectrum of two spins at Δ = 849,001 Hz and J = 24 Hz. These results can be applied to research interests for the medical world and as reference data for research standards.